2016
DOI: 10.3168/jds.2015-10546
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effect of soybeans roasted at different temperatures versus calcium salts of fatty acids on performance and milk fatty acid composition of mid-lactation Holstein cows

Abstract: To evaluate the effect of soybeans roasted at different temperatures on milk yield and milk fatty acid composition, 8 (4 multiparous and 4 primiparous) mid-lactation Holstein cows (42.9±3 kg/d of milk) were assigned to a replicated 4×4 Latin square design. The control diet (CON) contained lignosulfonate-treated soybean meal (as a source of rumen-undegradable protein) and calcium salts of fatty acids (Ca-FA, as a source of energy). Diets 2, 3, and 4 contained ground soybeans roasted at 115, 130, or 145°C, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
(118 reference statements)
4
9
0
1
Order By: Relevance
“…Our data for AI and TI were comparable to those previously obtained by other authors for goat cheese [54,68,69]. Rafiee-Yarandi et al [70] suggested that dairy products characterized by lower AI and TI values have a little incidence on the development of atherosclerosis and thrombosis in humans. In our study, we recorded the most interesting results in semi-hard cheese samples, where the AI and TI were significantly lower in farm M (2.25 and 2.52, respectively) than in farm O (2.84 and 2.84) and C (3.11 and 3.32).…”
Section: Resultssupporting
confidence: 91%
“…Our data for AI and TI were comparable to those previously obtained by other authors for goat cheese [54,68,69]. Rafiee-Yarandi et al [70] suggested that dairy products characterized by lower AI and TI values have a little incidence on the development of atherosclerosis and thrombosis in humans. In our study, we recorded the most interesting results in semi-hard cheese samples, where the AI and TI were significantly lower in farm M (2.25 and 2.52, respectively) than in farm O (2.84 and 2.84) and C (3.11 and 3.32).…”
Section: Resultssupporting
confidence: 91%
“…All the abovementioned indices together with PUFA/SFA and n-6/n-3 PUFA ratios are widely used to evaluate the nutritional value of milk fat. It is supposed that milk fat with high AI and TI values may be more likely to contribute to the development of atherosclerosis or coronary thrombosis in humans; whereas, milk with high HPI and HH ratios may have a protective effect against cardiovascular diseases [ 31 ]. Although a higher proportion of PUFA in milk fat is desirable from the perspective of human health, these can influence the technological properties of milk fat either positively (improved spreadability) or negatively (increased susceptibility to oxidation).…”
Section: Indices For Evaluation Of Milk Fat Qualitymentioning
confidence: 99%
“…Although animal factors evidently affect the FA profile of milk fat [ 18 ], the main factors are related to dairy cow nutrition [ 19 ]. A number of papers showing specific nutritional effects of cow diet on milk FA profiles have been published [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. These results regularly show that increasing the proportion of fresh (pasture) or preserved forage (generally fiber) as compared to grain concentrates and increasing the proportion of oilseeds in feed concentrates as compared to non-oleaginous seeds in dairy cow feeding rations improves the milk FA profile by increasing UFA and rumenic acid (RA; C18:2 c 9, t 11; isomer of conjugated linoleic acid (CLA)) content in milk fat.…”
Section: Introductionmentioning
confidence: 99%
“…FCS is an animal derived product of complex and unknown composition and contains serum of numerous donors pooled together. Numerous studies have proven that multiple factors (e.g., genetics, time of day, age, diet, and environment) can affect in the composition of cows milk of (e.g., concentration and type of lipids, nutrients, proteins, and antibodies) [55][56][57][58][59][60][61][62][63]. Like cow milk, FCS would likely have minor differences in growth factor composition/degradation depending on the specific herd of animals, season, food source, gestation of the fetuses, and as well as differences in serum collection, storage, and preparation methods.…”
Section: Caveats From This Studymentioning
confidence: 99%